An Elementary Proof for the Krull Dimension of a Polynomial Ring. Issue 7 (9th August 2018) - Nathanson, Melvyn B.
Abstract: It is proved that, for every infinite fieldF, the polynomial ringF [ t 1, …, tn ] has Krull dimension n . The proof uses only "high school algebra" and the rudiments of undergraduate "abstract algebra."